Impact on Survival with Immunotherapy and Evaluation of Biomarkers in Peruvian Patients with Advanced Melanoma - Valencia, G (2024)
Introduction: Advanced malignant melanoma is a very aggressive disease, historically with poor prognosis before the new advances with immunotherapy and targeted therapies that have changed the standard of care, especially in cutaneous melanoma. Peru has aggressive features such as higher rates of acral lentiginous melanoma (ALM) subtype with historically shorter survival. Methods: This study describes Peruvian patients with advanced melanoma treated with immunotherapy (nivolumab) in two oncological institutions (public and private), including the discussion of the impact on overall survival (OS) divided by subtype (with incidence in ALM histology) and potential biomarkers that could be related to prognosis. Results: We found that immunotherapy is safe, and improves progression-free survival (PFS), OS and objective response rate (ORR) in our patients, with lower benefit in ALM histology. No prognostic blood inflammatory biomarkers were detected. Discussion: There is very limited data of Peruvian patients with metastatic melanoma treated with immunotherapy, especially the outcomes in ALM histology. Our goal is to share an example of the impact of immunotherapy in a Latin American (LATAM) population considered as an unsatisfied group with an enormous need of novel treatments and biomarkers.